Hyperconnectivity and Spiritual Alienation: An Islamic Epistemological Approach to Cyberspace Ethics - Suhaily Amri Hasibuan; Rubino; Muhammad Randicha Hamandia; Zhila Jannati (Indonesian Journal Publisher, 2026)
This study examines the ethical crisis of hyperconnectivity and its implications for spiritual alienation within contemporary cyberspace. It argues that digital platforms are not neutral communication channels, but socio-technical environments shaped by algorithms, visibility, speed, and symbolic power. Through a qualitative library research design, this article analyzes recent national and international scholarship on digital ethics, Islamic epistemology, cyberculture, intrapersonal communication, and spiritual well-being. The study employs reflexive content analysis, critical discourse analysis, and philosophical hermeneutics to interpret the relationship between digital overload, post-truth communication, and the weakening of the qalb. The findings indicate that hyperconnectivity produces cognitive fragmentation, dependence on external validation, and a reduction of reflective practices such as tafakkur, muhasabah, and dhikr. To address this crisis, the article reconstructs Islamic communication ethics through the integrated lenses of Bayani, Burhani, and Irfani epistemology. Bayani ethics strengthens verification and truthful speech; Burhani ethics cultivates critical algorithmic literacy; and Irfani ethics protects spiritual intention and self-discipline. The study proposes a Theocentric-Anthropocentric model of cyberspace ethics, positioning digital interaction as a moral responsibility before God, the self, and society. This framework offers a spiritually grounded alternative to secular digital ethics by prioritizing truth, dignity, wisdom, and public benefit in online life today.